Decarbonising EU-Turkey energy cooperation: Challenges and prospects - Kadri Tastan (Stiftung Wissenschaft und Politik (SWP), 2022)
Russia's attack on Ukraine has once again highlighted Europe's heavy dependence on Russian natural gas and thus, among other things, underlined the significance of energy cooperation between the European Union (EU) and Turkey. Traditionally, Turkish-European energy relations have prioritised the diversification of energy resources in the face of Europe's dependence on Russia. The new emerging political, geopolitical, and energy context will have repercussions on Turkish-European energy relation. However, it is the ambitious process of decarbonisation of the economy and energy launched by the EU that will decisively shape the nature and future of Turkey-EU energy relations. Indeed, both European and Turkish interests related to energy security, energy affordability, and climate change mitigation require EU-Turkey cooperation in the decarbonisation process, which is expected to be very challenging. Energy transition is the key to medium- and long-term energy security for both sides.
Keywords: 320